I Would Not Have Made That Leap: Art as the Vehicle to Tell Your Story, Connect and Build Relationships (LEARNing Landscapes, 2024)
Our commentary includes an introduction to, and conversation sparked by, the Cree School Board’s Mikw Chiyâm, a secondary school program that engages in an artist-in-residence model. This is a dialogue between Melissa-Ann Pereira Ledo, settler queer educator/researcher/artist, and Siibii Petawabano, one of the first students who was part of the pilot program in the First Nation community of Mistissini in 2015. In 2021, after making “the leap” to become a professional artist-musician, Siibii returned to the program as one of the artists in residency themselves.
Keywords: Mikw Chiyâm